2015
DOI: 10.1111/tpj.12792
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of blood‐fleshed peach reveals activation of anthocyanin biosynthesis by NAC transcription factors

Abstract: SUMMARYAnthocyanin pigmentation is an important consumer trait in peach (Prunus persica). In this study, the genetic basis of the blood-flesh trait was investigated using the cultivar Dahongpao, which shows high levels of cyanidin-3-glucoside in the mesocarp. Elevation of anthocyanin levels in the flesh was correlated with the expression of an R2R3 MYB transcription factor, PpMYB10.1. However, PpMYB10.1 did not co-segregate with the blood-flesh trait. The blood-flesh trait was mapped to a 200-kb interval on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
323
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(361 citation statements)
references
References 69 publications
(81 reference statements)
12
323
0
Order By: Relevance
“…Recently, a PpBL gene (BLOOD) was indicated as a key regulator of anthocyanin biosynthesis in maturing blood-fleshed peach fruit (Zhou et al, 2015). It was shown to act as a heterodimer with another NAC family member, PpNAC1 (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a PpBL gene (BLOOD) was indicated as a key regulator of anthocyanin biosynthesis in maturing blood-fleshed peach fruit (Zhou et al, 2015). It was shown to act as a heterodimer with another NAC family member, PpNAC1 (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a PpBL gene (BLOOD) was indicated as a key regulator of anthocyanin biosynthesis in maturing blood-fleshed peach fruit (Zhou et al, 2015). It was shown to act as a heterodimer with another NAC family member, PpNAC1 (Zhou et al, 2015). In our study, the closest bilberry homolog for the peach BL gene, VmBL , showed a significant induction in its expression by ABA treatments as well as increased expression at the onset of bilberry fruit ripening slightly before VmTDR4 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of blood-fleshed P. persica uncovered a mechanism whereby BLOOD ( BL ) was the key gene for the blood-fleshed trait via its activation of PpMYB10.1 , and the silencing of BL reduced anthocyanin pigmentation in maturing fruits [6]. The MYB10 promoter is more variable in Malus × domestica “Honeycrisp” than in “Royal Gala”, which results in a more variable color pattern in the peel of the first cultivar [36].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting somatic cell lines contain pigments, including flavonoid, carotenoid, and betalain secondary metabolites, that can be directly visualized [4,5,6,7]. At the molecular level, chimeric variation was initially explained by the action of transposable elements (TEs, or transposons), or, more specifically, the Activator / Dissociation ( Ac / Ds ) system that regulates the mixture of purple and yellow pigments in maize kernels by activating or repressing a C group gene [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wang et al (2013) triggered the transcriptional gene silencing with TRV-based virus vectors in the young pear fruit skin. More recently, one report on TRV-based gene silencing in peach fruits was published in which silencing of NAC by VIGS led to the bleaching of the red-fleshed peach (Zhou et al 2015). Thus, plant virus vectors offer an attractive alternative method to study gene function especially related to fruit traits as well as to create transgenic plants especially in case of transformation-recalcitrant fruit trees.…”
Section: Introductionmentioning
confidence: 98%